Aging Strikes the Self-Face Advantage in Featural Processing. Issue 4 (8th August 2017) - Qian, Haoyue; Wang, Zhiguo; Yan, Lingyue; Gao, Xiangping
Abstract: Background/Study Context: The face is the most distinctive physical feature of a person. Previous work has shown that one's own face (self-face) is advantageous in perception. Here the authors investigate how aging influences the configural and featural processing of self-face. Methods: Older and young adults searched for their own faces and faces of strangers (Experiment 1) or acquaintances (Experiment 2) among distractor faces. The configural and featural processing of faces was assessed with face inversion in Experiment 1 and with changes in point of view in Experiment 2. Results: Experiment 1 revealed a robust self-face advantage for upright faces in both young and older adults. A similar advantage was observed for inverted faces in young but not in older adults. Experiment 2 revealed a self-face advantage in older adults regardless of the point of view; in young adults, however, the self-face advantage only emerged for frontal view faces. Conclusion: The present study shows that older adults have a self-face advantage in configural but not in featural processing. The authors suggest that the impairment in featural processing in older adults is likely the result of age-related changes in perceptual experience.